Pengaruh Isolasi Selimut Api Pasca-Pengelasan terhadap Perilaku Mekanik Sambungan Las FCAW pada Baja EH36 - Kurniawan, Ade Putra; Farida, Ida; Simanjuntak, Immanuel Heprianto (CV. IRA PUBLISHING, 2025)
Welding of EH36 steel, a widely used high-strength material in ship construction, may compromise joint toughness when post-weld cooling rates are not properly controlled, thereby affecting the fusion integrity between the weld metal and the base metal. This study investigates the effectiveness of a Fire Blanket as a post-weld thermal insulation method to regulate cooling rates and enhance the deformation resistance of welded joints. Two EH36 welded specimens were fabricated using the flux-cored arc welding (FCAW) process: one without insulation and the other covered with a Fire Blanket immediately after welding. The cooling behavior of both specimens was monitored, and joint performance was evaluated through a side bend test conducted in accordance with BKI standards to assess fusion quality and mechanical robustness. The results indicate that the Fire Blanket substantially reduced the cooling rate, with the insulated specimen reaching near-ambient temperature after approximately 270 minutes, compared with about 120 minutes under natural cooling. This moderated cooling resulted in superior deformation capacity, as evidenced by a higher maximum bending load of 50.0 kN for the insulated specimen, compared with 41.2 kN for the uninsulated specimen, representing an improvement of 21.3%. This study presents an experimental approach to evaluating the use of a Fire Blanket as a post-weld insulation technique for EH36 steel. The findings demonstrate that controlled cooling with thermal insulation can effectively improve weld-joint reliability in ship construction and may serve as a practical strategy for broader structural welding applications.